WO3 suportado em biomassa como catalisador para oxidação de sulfetos de alta eficiência - Yamakawa, Gabriel Franco (Universidade Federal de São Carlos, 2023)
The application of heterogeneous catalysis for the oxidation of sulfides is a widely utilized method for the conversion to sulfones. In thought of that, the present study assessed the application os a catalyst composed of tungsten oxide and chitosan biomass to obtain sulfones and sulfoxides, evaluating different reactional factor important to this reaction, analyzing the conversion and selectivity. The applied WO3 was obtained by the method of coprecipitation and was then immobilized to the chitosan support, evaluating the percentages of 10, 20, and 40% of m/m of WO3/chitosan. This material was analyzed by XRD, Raman, SEM and EDS. They showed that the obtained WO3 has a monoclinic crystalline structure, the chitosan showed a amorphous nature, characteristic of carbon based materials while the WO3/chitosan compounds showed a similar crystalline structure to the WO3. Through Raman spectra and SEM and EDS analysis, it was possible to observe that there was no homogeneity in the distribution of WO3 over the support. The W ratio in the materials was calculated and found that 18.92, 30.62, and 45.04% of their weight was W for the 10, 20, and 40% WO3/chitosan synthesized. It was possible to obtain the values of time, temperature, WO3 ratio, solvent, oxidant and mass of catalyst being them 60°C, 120 minutes, 20% of WO3, and 10 mg of catalyst with 2 mL of acetonitrile and 25 µL of H2O2 as the optimal conditions for the formation of over 98% of sulfones, while for sulfoxides, methanol was used instead of acetonitrile, reaching 80% of selectivity. Then, the stability of the catalyst was observed, allowing the scaling of the process, maintaining the values of conversion. Evaluating the scope, it was observed that the catalyst was efficient for the oxidation of seven other sulfides. Finally, a mechanism was suggested with a main contribution of the hydroperoxyl radical and the deficit of electronic density. Therefore, the obtained catalyst showed itself as an excellent alternative to be applied in sulfide oxidation reactions.
Biomass supported WO3 as a catalyst for highly efficient sulfides oxidation
Keywords: Oxidação; Sulfetos; Biomassa; WO3; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::FISICO QUIMICA INORGANICA